Obesity in menopause – our negligence or an unfortunate inevitability? - Kozakowski, Jarosław; Gietka-Czernel, Małgorzata; Leszczyńska, Dorota; Majos, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2017)
Numerous concerns about menopause exist among women, and fear of an increase in body weight is one of the most important of them. This paper presents an overview of current knowledge concerning the etiology of obesity related to menopause and about the mechanisms of its development, with particular regard to the hormonal changes that occur during this period of life. The role of estrogens in the regulation of energy balance and the effect of sex hormones on metabolism of adipose tissue and other organs are presented. The consequence of the sharp decline in the secretion of estrogens with subsequent relative hyperandrogenemia is briefly discussed. The main intention of this review is to clarify what is inevitable and what perhaps results from negligence and unhealthy lifestyles. In the last part of the paper the possibilities of counteracting the progress of adverse changes in body composition, by promoting beneficial lifestyle modifications and the use of hormonal substitution treatment, in cases where it is reasonable and possible, are described.